2011
DOI: 10.1007/s00167-011-1765-9
|View full text |Cite
|
Sign up to set email alerts
|

Revision ACL reconstruction: influence of a lateral tenodesis

Abstract: Retrospective case series, Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
122
1
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(132 citation statements)
references
References 40 publications
4
122
1
5
Order By: Relevance
“…Perhaps the best way to reconcile Dr. Baumfeld's call for randomized trials with Dr. Tashman's concerns about extraarticular procedures would be to focus on his idea that extra-articular procedures should not be used ''routinely,'' to identify those knees that might really benefit from the additional procedure, and then to compare anatomic ACL reconstructions with extra-articular procedures in only these situations. Based on our meta-analysis and recent relevant work [7][8][9], we believe those indications might include in knees at particular risk for failure, perhaps those with a Grade 3 pivot shift, those with chronic ACL lesions, and those presenting with a positive pivot shift after ACL reconstruction and undergoing revision as supported by recent studies. Additional indications could include (with some discretion and discussion needed in each case) high-level athletes, athletes who participate in pivoting sports, knees with a lateral femoral notch sign, those presenting with a Segond fracture, and revision procedures using intraarticular allograft material [5,[7][8][9].…”
supporting
confidence: 58%
See 1 more Smart Citation
“…Perhaps the best way to reconcile Dr. Baumfeld's call for randomized trials with Dr. Tashman's concerns about extraarticular procedures would be to focus on his idea that extra-articular procedures should not be used ''routinely,'' to identify those knees that might really benefit from the additional procedure, and then to compare anatomic ACL reconstructions with extra-articular procedures in only these situations. Based on our meta-analysis and recent relevant work [7][8][9], we believe those indications might include in knees at particular risk for failure, perhaps those with a Grade 3 pivot shift, those with chronic ACL lesions, and those presenting with a positive pivot shift after ACL reconstruction and undergoing revision as supported by recent studies. Additional indications could include (with some discretion and discussion needed in each case) high-level athletes, athletes who participate in pivoting sports, knees with a lateral femoral notch sign, those presenting with a Segond fracture, and revision procedures using intraarticular allograft material [5,[7][8][9].…”
supporting
confidence: 58%
“…Based on our meta-analysis and recent relevant work [7][8][9], we believe those indications might include in knees at particular risk for failure, perhaps those with a Grade 3 pivot shift, those with chronic ACL lesions, and those presenting with a positive pivot shift after ACL reconstruction and undergoing revision as supported by recent studies. Additional indications could include (with some discretion and discussion needed in each case) high-level athletes, athletes who participate in pivoting sports, knees with a lateral femoral notch sign, those presenting with a Segond fracture, and revision procedures using intraarticular allograft material [5,[7][8][9]. We believe that extraarticular additional procedures are only used in specific situations, rather than routinely.…”
supporting
confidence: 58%
“…19 Regardless of the fact that, so far, there is no research to suggest that ALL reconstruction improves the results of ACL reconstruction and the benefit of reconstructing this "new" structure is purely theoretical at this point, the addition of an extra-articular procedure for arthroscopic ACL reconstruction has yielded good results in several studies. [20][21][22][23] Vadalà et al 20 studied female athletes with ACL injuries and concluded that those who underwent extra-articular reinforcement had a lower rate of residual rotatory instability. Dejour et al 21 investigated the addition of the Lemaire procedure to ACL reconstruction with a patellar tendon and showed less anterior translation of the lateral plateau relative to intra-articular reconstruction alone.…”
Section: Discussionmentioning
confidence: 99%
“…Monaco et al 22 showed reduced internal rotation at 30 with the addition of a lateral plasty to single-band reconstruction when compared with double-band reconstruction alone. Trojani et al 23 studied revisions of ACL reconstructions in more than 160 patients and concluded that the addition of a lateral extra-articular procedure increased knee stability.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, authors (especially in Europe) who continued to combine ERs and IRs using hamstrings reported better clinical results, improved rotatory stability and higher Tegner scores, extra-articular reconstructions in aCl injuries J oints with no increased rate of complications, radiological signs of OA or arthrofibrosis. Moreover, all these authors continue to recommend the use of ERs in association with ACL reconstruction with hamstrings in patients with severe instability (pivot shift ++ or +++), female athletes, high-level/high-risk athletes and revision surgery cases (18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%